Ride, cowboy, ride! : 8 seconds ain't that long : a rodeo novel - Black, Baxter, 1945- (TwoDot, 2012)
"This hilarious new novel by America's best-selling cowboy poet, Baxter Black, offers a funny, fast-paced inside look at the lives of rodeo cowboys and the women they love--or that they want to love"--